INQUIRY METHOD ANALYSIS IN PROCESS LEARNING OF PEOPLE'S POETRY - Citra Amelia Sudiyati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
In an education, learning is supported by various methods, media, and learning models to improve the quality of learning. In this article, the author only focuses on one example of the method used to assist the teaching and learning process. The method is a way whose function is as a tool to achieve a goal. The better the method, the more effective the attainment of the goal. This writing aims to describe the inquiry method regarding the strengths and weaknesses in the process of learning folk poetry and the reconstruction of the inquiry method in the process of learning folk poetry. This writing is a non-research scientific article, where only the author's ideas are expressed. Compiled from several theories such as learning folk poetry, learning methods, learning methods in the 2013 curriculum, and related to inquiry learning methods. The results of this paper are found the weaknesses and strengths of the inquiry method in learning poetry and the weaknesses are reconstructed to make it better or more effective.